Literasi Keuangan, Inklusi Keuan PERAN LITERASI DAN INKLUSI KEUANGAN TERHADAP PENGEMBANGAN EKONOMI KREATIF DI KABUPATEN SUMENEP: Ekonomi Kreatif - Hanifiyah Rifadha; Susandini, Aprilina (Universitas Islam Lamongan, 2024)
The purpose of this study is to ascertain how financial inclusion and literacy contribute to the growth of the creative economy in Sumenep Regency. Fifty samples from actors in the Sumenep Regency's creative economy were used in this study. Quantitative research is the approach employed in this study. Primary data is the data source that was utilised. Information was gathered through the responses to questionnaires given to fifty participants in the creative economy. Simple random sampling, which is a probability sampling technique, was used to gather samples. The Likert scale is the measurement tool employed. With the use of SPSS (Statistical Product and Service Solution), to assess keabsahan hypotheses. The results of the uji hipotesis indicate that there is a significant influence between the literate class and the growth of the creative economy, while the influence between the inklusi class and the growth of the creative economy is not significant.